C–C Coupling in sterically demanding porphyrin environments - Cribbin, Liam; Twamley, Brendan; Buga, Nicolae; O’ Brien, John E.; Bühler, Raphael; Fischer, Roland A.; Senge, Mathias O. (Beilstein Journal of Organic Chemistry, 2024)
Unlike their planar counterparts, classic synthetic protocols for C–C bond forming reactions on nonplanar porphyrins are underdeveloped. The development of C–C bond forming reactions on nonplanar porphyrins is critical in advancing this field of study for more complex porphyrin architectures, which could be used in supramolecular assemblies, catalysis, or sensing. In this work a library of arm-extended dodecasubstituted porphyrins was synthesized through the optimization of the classic Suzuki–Miyaura coupling of peripheral haloaryl substituents with a range of boronic acids. We report on palladium-catalyzed coupling attempts on the ortho-, meta-, and para-meso-phenyl position of sterically demanding dodecasubstituted saddle-shaped porphyrins. While para- and meta-substitutions could be achieved, ortho-functionalization in these systems remains elusive. Furthermore, borylation of a dodecasubstituted porphyrin’s meso-phenyl position was explored and a subsequent C–C coupling showed the polarity of the reaction can be reversed resulting in higher yields. X-ray analysis of the target compounds revealed the formation of supramolecular assemblies, capable of accommodating substrates in their void.
Keywords: C–C coupling; conformational analysis; nonplanar porphyrin; Pd-catalysis; porphyrin